Response of fertility and agro-chemical on growth and yield of different varieties of clusterbean - Yogi, Rekha; Sharma, O.P.; Verma, H.P.; Kanwar, Krishna; Shivran, A.C. (Annals of Agricultural Research, 2016)
A field experiment was conducted during kharif season of 2013 to study response of clusterbeanvarieties to fertility levels and agro-chemicals at SKN College of Agriculture, Jobner. The experimentconsisted of two varieties (RGC-1038 and RGC-1066), three treatments of fertility levels (control,50% RDF and 100% RDF) and three treatments of agro-chemicals (control, thiourea 500 ppm twiceat vegetative and pre flowering stage and thiourea 100 ppm twice at vegetative and pre floweringstage) thereby making eighteen treatment combinations tested in randomized block design withthree replications. The results indicated that RGC 1066 variety recorded significantly higher plantheight 60 DAS and at harvest and dry matter per meter row length at 30 DAS, 60 DAS and atharvest, number of pods/plant and seeds/pod, test weight, seed, stover and biological yield ascompared to variety of RGC-1038. The result further indicated that application of 100% RDFsignificantly gave higher plant height at 60 DAS and at harvest similarly, dry matter per meter rowlength at 30 DAS, 60 DAS and at harvest, number of pods/plant and seeds/pod, test weight, seed,stover and biological yield recorded higher over control and 50% RDF. Likewise, application ofagro-chemical @ thiourea (500 ppm) significantly increased the plant height at 60 DAS and at harvestand dry matter per meter row length at 30 DAS, 60 DAS and at harvest, number of pods/plant andseeds/pod, weight, seed, stover yield and biological yield and remained at par with the applicationof agro-chemical @ TGA (100 ppm) over control. However, plant height at 30 DAS remainedmaterially unchanged under different varieties, fertility levels and agro-chemicals.